PENGEMBANGAN INSTRUMEN PENILAIAN HASIL BELAJAR ALQURAN HADIS DI MADRASAH ALIYAH NEGERI 3 MAKASSAR - Hardiyanti (AIJER: Algazali International Journal Of Educational Research, 2019)
Abstract: The Development of Instrument for Learning Outcomes of Al-Quran and Hadith Learning in Madrasah Aliyah Negeri 3 Makassar. This study aimed to develop an instrument for evaluating the learning outcomes of the Qur'an and hadith in Madrasah Aliyah in the realm of affective, cognitive and psychomotor. This research was an instrument development research that used 3D models and involved 252 subjects in class XI in Madrasah Aliyah Negeri 3 Makassar City. Data analysis techniques in content validation were carried out qualitatively using expert judgment and in empirical validation was inferential quantitative analysis and item analysis. The results showed that (1) the learning outcomes of the Qur'an and hadith were in the cognitive domain of class XI in Madrasah Aliyah Negeri 3 Makassar, in the form of a multiple choice test package 1 with 5 answer choices and 28 items and its reliability was 0.939 while the multiple choice test package 2 with 5 choices answers and 26 items and their reliability were 0.906 (2) The results of development of the instrument of learning assessment results of the Qur'an and hadith were in the affective domain of class XI in Madrasah Aliyah Negeri 3 Makassar, in the form of self-assessment scale with 27 statements and the reliability of 0.741 (3) The results of development of the instrument assessment of learning outcomes of the Qur'an and hadith were in the psychomotor domain of class XI in Madrasah Aliyah Negeri 3 Makassar in the form of performance, with 13 statements accompanied by an assessment rubric. Based on the results of calculation of content and empirical validity, these cognitive, affective, and psychomotor domain assessment instruments were stated to be accepted.